2011
DOI: 10.1029/2010ja015925
|View full text |Cite
|
Sign up to set email alerts
|

Vertical connection from the tropospheric activities to the ionospheric longitudinal structure simulated by a new Earth's whole atmosphere-ionosphere coupled model

Abstract: [1] This paper introduces a new Earth's atmosphere-ionosphere coupled model that treats seamlessly the neutral atmospheric region from the troposphere to the thermosphere as well as the thermosphere-ionosphere interaction including the electrodynamics selfconsistently. The model is especially useful for the study of vertical connection between the meteorological phenomena and the upper atmospheric behaviors. As an initial simulation using the coupled model, we have carried out a 30 day consecutive run in Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
133
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 39 publications
1
133
0
Order By: Relevance
“…Immel et al (2006) conclude that neutral winds in the lower atmosphere influence and modulate the E-region dynamo to produce spatial variability approximately 1,000 km scales. Other causes of EEJ variability suggested by earlier workers are (i) the variations in tidal strength (Stening 1975) and the sharp longitudinal gradients in the diurnal non-migrating tides (DE2 and DW2) between the longitudes over 15°separation (Anderson et al 2009); (ii) the day to day variability of zonal winds (Fang et al 2008); (iii) the day-to-day variability in semidiurnal tide at lower thermosphere, modulated by interactions at planetary wave periodicities (Fuller-Rowell et al 2008); and (iv) the modulation of ionospheric dynamo in the middle atmosphere through the excitation of solar non-migrating tides in the troposphere (Jin et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Immel et al (2006) conclude that neutral winds in the lower atmosphere influence and modulate the E-region dynamo to produce spatial variability approximately 1,000 km scales. Other causes of EEJ variability suggested by earlier workers are (i) the variations in tidal strength (Stening 1975) and the sharp longitudinal gradients in the diurnal non-migrating tides (DE2 and DW2) between the longitudes over 15°separation (Anderson et al 2009); (ii) the day to day variability of zonal winds (Fang et al 2008); (iii) the day-to-day variability in semidiurnal tide at lower thermosphere, modulated by interactions at planetary wave periodicities (Fuller-Rowell et al 2008); and (iv) the modulation of ionospheric dynamo in the middle atmosphere through the excitation of solar non-migrating tides in the troposphere (Jin et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In the future work, the ion temperatures obtained from the ESR observations will be compared with those simulated by our coupled whole atmosphere-ionosphere GCM, with which preliminary simulations (e.g., Jin et al, 2008Jin et al, , 2011 have been carried out.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the waves from below the ionosphere make a significant contribution to the day-to-day variability of the dynamo-region currents and ground-level Sq variations. Later studies, using improved dynamo models with more realistic neutral winds, have also underscored the importance of lower-atmospheric drivers in the short-term variability of the ionospheric dynamo (Kawano-Sasaki and Miyahara 2008;Jin et al 2011;Fang et al 2013; Yamazaki et al 2014a). Among those studies, Yamazaki et al (2014a) attempted to clarify where the day-to-day variability of the equatorial electrojet is produced.…”
Section: Irregular Changesmentioning
confidence: 99%